Menyelami Metode Pendidikan Humanistik Sosaku Kobayashi Dalam Novel Totto Chan: The Little Girl At The Window Karya Tetsuko Kuroyanagi - Apri Damai Sagita Krissandi (IZUMI, 2019)
(Understanding The Education Method Of Sasoko Kobayashi In Novel Totto Chan: The Little Girl At The Window By Tetsuko Kuroyanagi) This study was aimed to describe the humastic educational method applied by Sosaku Kobayashi at Tomoe Gakuen school in Totto Chan's novel: The Litle Girl At The Window by Tetsuko Kuroyanagi. The method used in this research was descriptive. Based on the analysis of the study of Totto Chan's novel: The Litle Girl At The Window by Tetsuko Kuroyanagi, it can be concluded that the educational method applied by Sosaku Kobayashi at Tomoe Gakuen school was a method of humanistic education including ways to create authentic personality such as (1) strengthen students' confidence in giving meaning to life  (2) paving the way for self-development, based on freedom and responsibility, (3) guiding learners to find life with self-motivation and desire to become more, (4) developing a worldview in a way original and expression in accordance with the students themselves. The four things can be seen through the learning activities in the classroom, learning activities outside the classroom, school rules, and the role of educators in learning.   gb777gb777slot gacorgb777gb777GB777GB777slot gacorslot gacor